(untitled) (Texas Journal of Medical Science, 2022)
The need for a morphological study of the structure of the stomach wall is dictated by the fact that the end of the 20th century is characterized by a sharp increase in the number of diseases of the stomach. In the USA in 1997, 140,000 patients with gastric bleeding L. Laine (2002) were hospitalized. In Russia in 1999, 64,000 patients with gastrointestinal bleeding were hospitalized, which is almost 2.2 times more than in 1990 (statistical materials of the Ministry of Health. RF. 2000).